Utilization of Fish Skin Waste for Enhancing Knowledge and Skills of Homemakers in Talang Keramat Village - Riya Liuhartana Nasyiruddin; Rih Laksmi Utpalasari; Sofian Sofian; Fitra Mulia Jaya; Indah Anggraini Yusanti; Neny Rochyani; Rahma Mulyani; Rr Dyah Paramitha Mentari; Zhulian Hikmah Hasibuan; Willard Burton Navicha; Dewi Duta Anggeraini; Andrian Syaputra (Asosiasi Profesi Multimedia Indonesia, 2025)
This community service in Talang Keramat Village, South Sumatra, Indonesia, aimed to empower homemakers by valorising fish skin waste. The primary objective was to promote its use in processed food to improve nutrition and economic prospects. The project specifically sought to: (1) enhance understanding of fish skin's potential as a raw material for nutritious and economically viable food; (2) demonstrate practical methods for processing fish skin into food products; and (3) shift community perception regarding the benefits of utilizing fish skin waste. A descriptive qualitative approach was employed, with implementation in three phases: pre- and post-test questionnaires to assess comprehension; educational material on transforming fish skin waste; and a demonstration of processed food preparation. Sixteen homemakers participated in the one-day activity. Results showed that 75.00% understood the nutritional and economic value of fish skin waste, 81.25% could explain processing methods, and 87.50% showed improved understanding of its benefits. In conclusion, this community service successfully empowered homemakers with the knowledge and skills to convert fish waste into valuable food products, contributing to nutritional enhancement and economic empowerment within the community.